Preparation and Evaluation of Pear and Grapes Blended Leather: Preparation of Pear and Grapes Blended Leather - Ahmad, Ishtiaq; Riaz, Aysha; Khan, Arsalan; Shah, Syed Sohail; Shah, Falak Naz; Zeeshan, Muhammad (Biological Sciences - PJSIR, 2021)
Pear pulp and grapes juice were used in different ratios (100:0, 90:10, 80:20, 70:30, 60:40, 50:50) for the preparation of leather. The treatments were prepared with different concentration of pulp and constant level of sucrose and preservatives. The experiment was laid out in a complete randomized design (CRD). The effects of storage and treatments were studied for three months of storage with an interval of 15 days. Various parameters such as moisture, percent acidity, total soluble solids, water activity, ascorbic acid content, reducing sugar, non-reducing sugar and sensory attributes i.e. colour, taste, texture and overall acceptability were studied. Significant differences were observed in all the studied parameters. A decrease was recorded in moisture (16.02 to 13.76%), ascorbic acid content (13.21 to 6.64 mg/100g), non-reducing sugar (67.02 to 64.76%) and water activity (0.50 to 0.45), while an increase was recorded in titratable acidity (0.88 to 1.01%), TSS (76.68 to 79.05 °brix) and reducing sugar (11.43 to 11.85%). Base on organoleptic evaluation T3 was found most acceptable during storage. The combination of 70% pear pulp and 30% grapes juice for leather preparation proved to be the best combination in terms of extending the shelf life and improving the quality of pear and grapes blended leather during storage.